Reliability of measures of lower-body strength and speed in academy male adolescent soccer players - Ferguson, J.; Gibson, N. V.; Weston, M.; McCunn, R. (The Journal of Strength and Conditioning Research, 2024)
The Nordbord and ForceFrame represent a practical and time efficient means of assessing eccentric hamstring and isometric adductor strength in the large number of squads and players associated with youth soccer academies, yet measurement reliability in this population is unexamined. Therefore, over a period of 4 days, with no less than 24 hours and no more than 48 hours between trials, 37 players (age: 14.7 ± 0.8 years, stature: 168.7 ± 7.8 cm, mass: 57.7 ± 9.1 kg, and maturity offset: 0.8 ± 0.9 years) were assessed for eccentric hamstring strength (force, torque), isometric adductor strength (long and short lever positions), and 30-m sprint (5, 10, and 20-m splits), using the Nordbord, ForceFrame, and electronic timing gates, respectively, on 3 separate occasions. Relative reliability (intraclass correlation coefficient) was rated as good for all Nordbord (range: 0.86-0.89) and ForceFrame (0.78-0.85) measures and ranged from moderate (0.53) to excellent (0.93) for the speed measures, improving with increased distance. Absolute reliability (standard error of the measurement [%SEM]) ranged from 7 to 8% (Nordbord), 3 to 11% (ForceFrame), and 1 to 4% (sprints). Our data provide the first Nordbord and ForceFrame reliability estimates in adolescent soccer academy players. To interpret test sensitivity, practitioners are encouraged to interpret our estimates of absolute reliability against meaningful change values derived from personal experience and evidence-based knowledge and not against absolute or standardized thresholds.